Pemberdayaan Keluarga Dalam Pemulihan Stroke "Cerdas Dalam Mengenal Dan Merawat Penderita Stroke Dirumah" - Windi Kartika (2021)
Stroke is the loss of brain function due to blocked or ruptured brain blood vessels, which can cause the death of some brain cells. Stroke is also the second leading cause of death and the third leading cause of disability in the world. Stroke patients will experience physical limitations and dependence in carrying out daily activities or Activities of Daily Living (ADL). Meeting the daily needs of stroke patients during home care will generally be assisted by family members. This booklet contains the concept of stroke, namely the understanding, causes, classification, symptoms of stroke, treatment for the first attack that can be carried out by the family, complications, ways to prevent and change body functions that families need to know so that they can add information for families in caring for stroke patients at home. In addition, this booklet also provides information for families in providing the care needed by stroke patients starting from support, family roles, disorders that occur, tips for healthy living after stroke as well as simple activities and exercises that families can provide to improve daily activities for patients. strokes. Treatment of stroke patients by the family certainly requires knowledge and understanding of stroke care, with the information on caring for stroke patients at home in this booklet, it is expected to provide additional insight and help families in providing care for stroke patients at home.